Pengembangan Sistem Informasi Pelaporan BPHTB Pada Badan Pendapatan Daerah Kabupaten Bondowoso - Ridho Robby Prestisiadi; Ismiarta Aknuranda; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Regional Income Agency (BPD) Bondowoso on duty to assist the Regent of perceived Government Affairs District in the area of revenue. In its implementation, the BPD Bondowoso has several tasks, one of which is the process of reporting BPHTB (Bea acquisition of Rights over the land and buildings). Reporting BPHTB do when the existence of the buying and selling of land/buildings. Buyers are required to do reporting BPHTB over land/buildings are purchased. However, in its application, there are several problems faced by Taxpayers nor the parties BPD Bondowoso. BPD Bondowoso has no institutions survey to determine the market value of any land/building reported in BPHTB, so Taxpayers should come to Tax Service Office (KPP Pratama) Pratama Situbondo to do validation of the value of land/buildings. In addition, in the process of reporting BPHTB, Taxpayers need to fill as many as six BPHTB form sheet. The second page until the last page is a duplicate of the first page but are aimed at different things. Another issue is BPD Bondowoso still keep documents reporting BPHTB manual way which causes easy file is damaged. Based on the problem then the solution that can be applied is to create a system of Information Reporting BPHTB. The system will use the method of the Quality Rating to calculate the market value ofland/buildings. The system is developed with waterfall. Testing was done using the validation testing, compatibility testing and calculation of Quality Rating to prove that the system has been going according to user needs, capable of running on a variety of browsers, as well as having the accuracy of calculations Quality Rating.